Economic Loss from Nematodiasis in Local Goat Farmings around the Region of Animal Primary Health Care of Batee Roo, Aceh Jaya Regency - Murhaban Murhaban; Teuku Reza Ferasyi; Muhammad Hambal; Yudha Fahrimal; Razali Razali (The International Journal of Tropical Veterinary and Biomedical Research, 2017)
This study aims to dicover the economic loss caused by nematodiasis in local goat farmings around the animal primary health care (Puskeswan) in Batee Roo, Aceh Jaya. In this study, as many as 84 goats positive of nematodiasis were used as samples for cross-sectional approach. Nematodiasis goats were confirmed from clinical symptoms and fecal examination using centrifugation method. Economic loss was determined by measuring body weight of all the goats. The results showed that the goats in the local farms had more than 70% prevalence rate of nematodiasis, which caused economic loss around Rp. 34.300,-/male goat, and Rp.9.310,-/ female goat. Based on the goats population in Batee Roo in 2014, total economic loss from nematodiasis for male goats reached Rp. 19.012.000,- per year, and for female it was Rp. 9.012.000,- per year. From this data, it can be concluded that the economic loss from nematodiasis in male and female goats around Puskeswan Batee Roo, Aceh Jaya per year could reach Rp. 20.000.000.